KAPLAN-MEIER AND NELSON-AALEN ESTIMATORS FOR CREDIT SCORING - Tatik Widiharih; Agus Rusgiyono; Sudarno Sudarno; Bagus Arya Saputra (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2023)
Financial institutions use credit scoring analysis to predict the probability that a customer will default. In this paper, we determine the probability of default using nonparametric survival analysis that are Kaplan-Meier and Nelson-Aalen. The analysis is based on survival function curves, cumulative hazard function curves, mean survival time, and standard error of estimators. Based on the curves of survival function for both Kaplan Meier and Nelson Aalen estimators relatively the same. Based on the curves of cumulative hazard function, mean survival time, and standard error the Nelson-Aalen estimators are slightly higher than Kaplan-Meier.